Pecuniary externalities, bank overleverage, and macroeconomic fragility - Ryo Kato; Takayuki Tsuruga (Osaka University, Institute of Social and Economic Research (ISER), 2020)
Pecuniary externalities in models with financial friction justify macroprudential policies for preventing economic agents'excessive risk taking. We extend the Diamond and Rajan (2012) model of banks with the production factors and explore how a pe- cuniary externality affects a bank's leverage. We show that the laissez-faire banks in our model take on excessive risks compared with the constrained social optimum. Our numerical simulations suggest that the crisis probability is 2-3 percentage points higher in the laissez-faire economy than in the constrained social optimum.
Keywords: E3; G01; G21; 330; Financial crisis; Liquidity shortage; Maturity mismatch; Credit externalities; Financial regulation